Efektivitas Praktikum Industri Perjalanan Di Masa Pandemi - I Gusti Ketut Indra Pranata Darma; Ni Made Rai Kristina (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
Practicum as one of the learning media is a process that is eagerly awaited by every student. The practicum process makes the application of theory in school even to finding new theories based on recent research with certain variables. Travel industry practicum as a form of learning for tourism students, becomes a synchronization of theory with practice in the field. At present, the travel industry practicum that runs during the COVID-19 pandemic is a challenge. How to carry out learning in the field but stay safe from the covid-19 virus. This research will try to explore the level of effectiveness in carrying out the travel industry practicum with all its problems during the covid-19 pandemic. It is hoped that after digging up information about the effectiveness of the practicum, it is possible to make a model that can be applied during a special period as it is currently happening.